Erratum to: Determination of critical cooling rates in metallic glass forming alloy libraries through laser spike annealing (Scientific Reports, (2017), 7, 1, (7155), 10.1038/s41598-017-07719-2) - Bordeenithikasem, P.; Liu, J.; Kube, S.A.; Li, Y.; Ma, T.; Scanley, B.E.; Broadbridge, C.C.; Vlassak, J.J.; Singer, J.P.; Schroers, J. (Scientific Reports, 2018)
A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has not been fixed in the paper. © 2018, The Author(s).
Keywords: dept.phy; erratum; error

Speckle imaging through a coherent fiber bundle - Davidson, J.W., Jr.; Horch, E.P.; Majewski, S.R. (SPIE, 2018)
Speckle imaging is a well known method to achieve diffraction-limited (DL) imaging from ground-based telescopes. The traditional observing method for speckle has been to observe a single, unresolved, source per telescope pointing over a relatively small field of view (FOV). The need for large DL surveys of targets with high sky density motivates a desire for simultaneous speckle imaging over large FOVs, however it is currently impractical to attain this by covering the entire focal plane with fast readout detectors. An alternative approach is to connect a relatively small number of detector pixels to multiple interesting targets spanning a large FOV through the use of optical fibers, a technique employed in spectroscopy for decades. However, for imaging we require the use of coherent fiber bundles (CFBs). We discuss various design considerations for coherent fiber speckle imaging with an eye toward a multiplexed system using numerous configurable CFBs, and we test its viability with a prototype instrument that uses a single CFB to transport speckle images from the telescope focal plane to a traditionally designed, fast readout speckle camera. Using this device on University of Virginia's Fan Mountain Observatory 40-inch telescope we have for the first time successfully demonstrated speckle imaging through a CFB, using both optical and NIR detectors. Results are presented of DL speckle imaging of well-known close (including subarcsecond) binary stars resolved with this fiber-fed speckle system and compared to both literature results and traditional speckle imaging taken with the same camera directly, with no intervening CFB. © 2018 SPIE.
Keywords: Binary star; Cameras; Coherent fiber bundles; Exo-planets; Fiber optics; Focusing; High-resolution imaging; Interferometry; Optical fibers; Speckle; Speckle imaging; Stars; Telescopes; binary stars; coherent fiber bundles; dept.phy; exo-planets; fiber optics; high resolution imaging

Two-color speckle imaging of M-dwarfs with the Discovery Channel telescope - Hahne, F.W.; Horch, E.P.; Van Belle, G.T.; Clark, C.; Winters, J.G.; Henry, T.J. (SPIE, 2018)
Lowell Observatory and Southern Connecticut State University are currently involved in a joint project to determine the stellar multiplicity rates and the fundamental stellar parameters of M dwarf stars using the Differential Speckle Survey Instrument (DSSI) at Lowell's Discovery Channel Telescope (DCT). DSSI observes speckle patterns simultaneously at two separate wavelengths, allowing color measurements of the components of a binary system to be made in a single observation. This paper will describe the initial data gathering process, which began in 2016. Since then, over 1000 stars have been observed. We summarize the analysis on these objects so far, and discuss the relevance of these observations for existing and future space missions such as TESS, JWST, and Gaia. © 2018 SPIE.
Keywords: Color measurements; Discovery channel telescopes; Image reconstruction; Interferometry; Multiplicity rate; Optical properties; Speckle; Speckle imaging; Speckle patterns; Stars; Stellar parameters; Survey instruments; Telescopes; dept.phy; image reconstruction; stellar properties

Azimuthal anisotropy in Cu+Au collisions at s NN =200 GeV - STAR Collaboration (Physical Review C, 2018)
The azimuthal anisotropic flow of identified and unidentified charged particles has been systematically studied in Cu+Au collisions at sNN=200 GeV for harmonics n=1-4 in the pseudorapidity range |η|<1. The directed flow in Cu+Au collisions is compared with the rapidity-odd and, for the first time, the rapidity-even components of charged particle directed flow in Au+Au collisions at sNN=200 GeV. The slope of the directed flow pseudorapidity dependence in Cu+Au collisions is found to be similar to that in Au+Au collisions, with the intercept shifted toward positive pseudorapidity values, i.e., the Cu-going direction. The mean transverse momentum projected onto the spectator plane (px) in Cu+Au collision also exhibits approximately linear dependence on pseudorapidity with the intercept at about η≈-0.4 (shifted from zero in the Au-going direction), closer to the rapidity of the Cu+Au system center of mass. The observed dependencies find a natural explanation in a picture of the directed flow originating partly due the "tilted source" and partly due to the asymmetry in the initial density distribution. A charge dependence of (px) was also observed in Cu+Au collisions, consistent with an effect of the initial electric field created by charge difference of the spectator protons in two colliding nuclei. The rapidity-even component of directed flow in Au+Au collisions is close to that in Pb+Pb collisions at sNN=2.76 TeV, indicating a similar magnitude of dipolelike fluctuations in the initial-state density distribution. Higher harmonic flow in Cu+Au collisions exhibits similar trends to those observed in Au+Au and Pb+Pb collisions and is qualitatively reproduced by a viscous hydrodynamic model and a multiphase transport model. For all harmonics with n≥2 we observe an approximate scaling of vn with the number of constituent quarks; this scaling works as well in Cu+Au collisions as it does in Au+Au collisions. © 2018 American Physical Society.
Keywords: dept.phy; peer-reviewed

Global polarization of Λ hyperons in Au + Au collisions at sNN =200 GeV - STAR Collaboration (Physical Review C, 2018)
Global polarization of Λ hyperons has been measured to be of the order of a few tenths of a percentage in Au+Au collisions at sNN = 200 GeV, with no significant difference between Λ and Λ. These new results reveal the collision energy dependence of the global polarization together with the results previously observed at sNN = 7.7-62.4 GeV and indicate noticeable vorticity of the medium created in noncentral heavy-ion collisions at the highest Relativistic Heavy Ion Collider collision energy. The signal is in rough quantitative agreement with the theoretical predictions from a hydrodynamic model and from a multi-phase transport model. The polarization is larger in more peripheral collisions, and depends weakly on the hyperon's transverse momentum and pseudorapidity ηH within |ηH|<1. An indication of the polarization dependence on the event-by-event charge asymmetry is observed at the 2σ level, suggesting a possible contribution to the polarization from the axial current induced by the initial magnetic field. © 2018 American Physical Society.
Keywords: dept.phy; peer-reviewed

Improved measurement of the longitudinal spin transfer to Λ and Λ hyperons in polarized proton-proton collisions at s =200 GeV - STAR Collaboration (Physical Review D, 2018)
The longitudinal spin transfer DLL to Λ and Λ hyperons produced in high-energy polarized proton-proton collisions is expected to be sensitive to the helicity distribution functions of strange quarks and antiquarks of the proton, and to longitudinally polarized fragmentation functions. We report an improved measurement of DLL from data obtained at a center-of-mass energy of s=200 GeV with the STAR detector at RHIC. The data have an approximately twelve times larger figure of merit than prior results and cover |η|<1.2 in pseudorapidity with transverse momenta pT up to 6 GeV/c. In the forward scattering hemisphere at largest pT, the longitudinal spin transfer is found to be DLL=-0.036±0.048(stat)±0.013(sys) for Λ hyperons and DLL=0.032±0.043(stat)±0.013(sys) for Λ antihyperons. The dependences on η and pT are presented and compared with model evaluations. © 2018 authors. Published by the American Physical Society.
Keywords: dept.phy; peer-reviewed

Low- pT e+e- Pair Production in Au +Au Collisions at sNN =200 GeV and U + U Collisions at sNN =193 GeV at STAR - STAR Collaboration (Physical Review Letters, 2018)
We report first measurements of e+e- pair production in the mass region 0.4<Mee<2.6 GeV/c2 at low transverse momentum (pT<0.15 GeV/c) in noncentral Au+Au collisions at sNN=200 GeV and U+U collisions at sNN=193 GeV. Significant enhancement factors, expressed as ratios of data over known hadronic contributions, are observed in the 40%-80% centrality of these collisions. The excess yields peak distinctly at low pT with a width (âpT2â ©) between 40 and 60 MeV/c. The absolute cross section of the excess depends weakly on centrality, while those from a theoretical model calculation incorporating an in-medium broadened ρ spectral function and radiation from a quark gluon plasma or hadronic cocktail contributions increase dramatically with an increasing number of participant nucleons. Model calculations of photon-photon interactions generated by the initial projectile and target nuclei describe the observed excess yields but fail to reproduce the pT2 distributions. © 2018 authors. Published by the American Physical Society. Published by the American Physical Society under the terms of the »https://creativecommons.org/licenses/by/4.0/» Creative Commons Attribution 4.0 International license. Further distribution of this work must maintain attribution to the author(s) and the published article's title, journal citation, and DOI. Funded by SCOAP3.
Keywords: Au+Au collisions; Colliding beam accelerators; Enhancement factor; Germanium compounds; Gold; Mass regions; Measurements of; Pair production; Photons; Transverse momenta; dept.phy; peer-reviewed

Transverse spin transfer to Λ and Λ hyperons in polarized proton-proton collisions at s =200 GeV - STAR Collaboration (Physical Review D, 2018)
The transverse spin transfer from polarized protons to Λ and Λ hyperons is expected to provide sensitivity to the transversity distribution of the nucleon and to the transversely polarized fragmentation functions. We report the first measurement of the transverse spin transfer to Λ and Λ along the polarization direction of the fragmenting quark, DTT, in transversely polarized proton-proton collisions at s=200 GeV with the STAR detector at RHIC. The data correspond to an integrated luminosity of 18 pb-1 and cover the pseudorapidity range |η|<1.2 and transverse momenta pT up to 8 GeV/c. The dependence on pT and η are presented. The DTT results are found to be comparable with a model prediction and are also consistent with zero within uncertainties. © 2018 authors. Published by the American Physical Society.
Keywords: dept.phy; peer-reviewed

Speckle imaging of KOI binary stars with the WIYN telescope - Hess, N.M.; Thayer, P.R.; Horch, E.P.; Davidson, J.W., Jr.; Baptista, B.J.; Everett, M.E.; Howell, S.B. (SPIE, 2018)
Binary star systems where one of the stars is an exoplanet host appear to be more common than expected prior to the Kepler mission. The Kepler mission and subsequent ground-based follow-up work have revealed a number of Kepler Objects of Interest (KOIs) that have nearby stellar companions (within ∼1 arcsec). KOIs with stellar companions and at least one suspected exoplanet were selected for this work. Recent work on these stars has mainly focused on placing the companions on the H-R diagram and inferring if they are likely to be gravitationally bound based on whether their locations are consistent with a common isochrone. However, we have been observing these KOI double stars with speckle imaging over several years and are now in a position to assess whether these systems have components with a common proper motion, and can be seen as physically associated on that basis. We will give sample results of KOI double stars that are in fact common proper motion pairs. We compare our results with estimates of the multiplicity rate of exoplanet hosts from other methods and comment on the use of our data for constraining orbital parameters at this point, particularly the inclination angle. For transit observations, the inclination of the planetary orbit is already known, and the relationship between planetary and stellar orbital planes could have implications for star and planet formation. © 2018 SPIE.
Keywords: Binary star; Binary star system; Extrasolar planets; Host-stars; Inclination angles; Interferometry; Multiplicity rate; Orbital parameters; Orbits; Speckle; Speckle imaging; Stars; astrometry; binary stars; dept.phy; exoplanet host stars

Preface - Jain, F.; Broadbridge, C.; Gherasimova, M.; Tang, H. (International Journal of High Speed Electronics and Systems, 2018)
Keywords: dept.phy

Preface - Jain, F.; Broadbridge, C.; Tang, H.; Gherasimova, M. (International Journal of High Speed Electronics and Systems, 2018)
Keywords: dept.phy

Preface - Jain, F.C.; Broadbridge, C.; Tang, H.; Gherasimova, M. (High Performance Materials and Devices for High-Speed Electronic Systems, 2018)
Keywords: Materials; dept.phy

Machine learning based analysis of human prostate cancer cell lines at different metastatic ability using native fluorescence spectroscopy with selective excitation wavelength - Xue, J.; Pu, Y.; Smith, J.; Gao, X.; Wu, B. (SPIE, 2018)
Native fluorescence spectra play important roles in cancer detection. It is widely acknowledged that the emission spectrum of a tissue is a superposition of spectra of various salient fluorophores. However, component quantification is essentially an ill-posed problem. To address this problem, the native fluorescence spectra of normal human very low (LNCap), moderately metastatic (DU-145), and advanced metastatic (PC-3) cell lines were studied by the selected wavelength of 300 nm to investigate the key fluorescent molecules such as tryptophan, collagen and NADH. The native fluorescence spectra of cancer cell lines at different risk levels were analyzed using various machine learning algorithms for feature detection and develop criteria to separate the three types of cells. Principal component analysis (PCA), nonnegative matrix factorization (NMF), and partial least squares fitting were used separately to reduce dimension, extract features and detect biomolecular alterations reflected in the spectra. The scores corresponding to the basis spectra were used for classification. A linear support vector machine (SVM) was used to classify the spectra of the cells with different metastatic ability. In detection of signals coming from tryptophan and NADH with observed data corrupted by noise and inference, a sufficient statistic can be obtained based on the basis spectra retrieved using nonnegative matrix factorization. This work shows changes of relative contents of tryptophan and NADH obtained from native fluorescence spectroscopy may present potential criteria for detecting cancer cell lines of different metastatic ability. © 2018 SPIE.
Keywords: Amino acids; Artificial intelligence; Cell culture; Cells; Diseases; Emission spectroscopy; Factorization; Feature extraction; Fluorescence; Fluorescence spectroscopy; Image retrieval; Learning algorithms; Least squares approximations; Matrix algebra; NADH; Native fluorescence; Native fluorescence (NFL) spectra; Nonnegative matrix factorization; Photonics; Principal component analysis; Spectrum analysis; Support vector machines; advanced metastatic (PC-3); dept.phy; low metastatic (LNCap); moderately metastatic (DU-145); nonnegative matrix factorization; principal component analysis; support vector machine (SVM) classifier; tryptophan

Beam-Energy Dependence of Directed Flow of Λ, Λ , K±, Ks0, and φ in Au+Au Collisions - STAR Collaboration (Physical Review Letters, 2018)
Rapidity-odd directed-flow measurements at midrapidity are presented for Λ, Λ, K±, Ks0, and φ at sNN=7.7, 11.5, 14.5, 19.6, 27, 39, 62.4, and 200 GeV in Au+Au collisions recorded by the Solenoidal Tracker detector at the Relativistic Heavy Ion Collider. These measurements greatly expand the scope of data available to constrain models with differing prescriptions for the equation of state of quantum chromodynamics. Results show good sensitivity for testing a picture where flow is assumed to be imposed before hadron formation and the observed particles are assumed to form via coalescence of constituent quarks. The pattern of departure from a coalescence-inspired sum rule can be a valuable new tool for probing the collision dynamics. © 2018 authors. Published by the American Physical Society.
Keywords: Au+Au collisions; Beam energies; Colliding beam accelerators; Collision dynamics; Directed flow; Elementary particles; Equation of state; Equations of state; Germanium compounds; Gold compounds; Heavy ions; High energy physics; Quantum chromodynamics; Quantum theory; Relativistic Heavy Ion Collider; Tracker detector; dept.phy; peer-reviewed

Invited Article: Molecular biomarkers characterization for human brain glioma grading using visible resonance Raman spectroscopy - Zhou, Yan; Liu, Cheng-hui; Wu, Binlin; Zhang, Chunyuan; Yu, Xinguang; Cheng, Gangge; Chen, Hong; Li, Shenglin; Liang, Qijun; Zhang, Mingqian; Zhu, Ke; Shi, Lingyan; et al. (APL Photonics, 2018)
The accurate identification of the human brain tumor boundary and the complete resection of the tumor are two essential factors for the removal of the glioma tumor in brain surgery. We present a visible resonance Raman (VRR) spectroscopy technique for differentiating the brain tumor margin and glioma grading. Eighty-seven VRR spectra from twenty-one human brain specimens of four types of brain tissues, including the control, glioma grade II, III, and IV tissues, were observed. This study focuses on observing the characteristics of new biomarkers and their changes in the four types of brain tissue. We found that two new RR peaks at 1129 cm-1 and 1338 cm-1 associated with molecular vibrational bonds in four types of brain tissues are significantly different in peak intensities of VRR spectra. These two resonance enhanced peaks may arise from lactic acid/phosphatidic acid and adenosine triphosphate (ATP)/nicotinamide adenine dinucleotide, respectively. We found that lactic acid and ATP concentrations vary with glioma gratings. The higher the grade of malignancy, the more the increase in lactic acid and ATP concentrations. These two RR peaks may be considered as new molecular biomarkers and used to evaluate glioma grades and identify the margin of gliomas from the control tissues. The metabolic process of lactic acid and ATP in glioma cells based on the VRR spectral changes may reveal the Warburg hypothesis. © 2018 Author(s).
Keywords: Adenosinetriphosphate; Biomarkers; Brain; Control tissues; Grading; Histology; Human brain tumors; Lactic acid; Metabolic process; Molecular biomarker; Resonance; Resonance Raman; Resonance Raman spectroscopy; Resonance enhanced; Spectral change; Tumors; dept.phy; peer-reviewed

J/ψ production cross section and its dependence on charged-particle multiplicity in p + p collisions at √s=200 GeV - STAR Collaboration (Physics Letters B, 2018)
We present a measurement of inclusive J/ψ production at mid-rapidity (|y|¡1) in p+p collisions at a center-of-mass energy of s=200 GeV with the STAR experiment at the Relativistic Heavy Ion Collider (RHIC). The differential production cross section for J/ψ as a function of transverse momentum (pT) for 0¡pT¡14 GeV/c and the total cross section are reported and compared to calculations from the color evaporation model and the non-relativistic Quantum Chromodynamics model. The dependence of J/ψ relative yields in three pT intervals on charged-particle multiplicity at mid-rapidity is measured for the first time in p+p collisions at s=200 GeV and compared with that measured at s=7 TeV, PYTHIA8 and EPOS3 Monte Carlo generators, and the Percolation model prediction.
Keywords: Charged-particle multiplicity; Multiple parton interactions; Quarkonium; collisions; dept.phy; p+p collisions; peer-reviewed

The Three-dimensional orbit, orbital parallax, and individual masses of the double-lined spectroscopic binaries HD 183255, HD 114882, and HD 30712 - Docobo, J. A.; Campo, P. P; Gomez, J.; Horch, Elliott P. (The Astronomical Journal, 2018)
Recent speckle observations performed at the Discovery Channel Telescope, the Gemini North Telescope, and the Special Astrophysical Observatory 6 m Telescope have permitted us to calculate the visual orbit of SB2 HD 114882 for the first time and to improve the visual orbits of two other SB2 systems, HD 30712 and HD 183255, using algorithms published by the authors of this research. Recently, new high-quality spectroscopic orbits have been obtained for these binaries by other authors. We determine their 3D orbits, individual masses, and orbital parallaxes, and present them in this paper. The parallaxes are compared with those available from the Gaia mission, and a comparison between the values confirms the precision of the results obtained here. © 2018. The American Astronomical Society. All rights reserved.
Keywords: astrometry; binaries: spectroscopic; binaries: visual; dept.phy; peer-reviewed; stars: fundamental parameters; techniques: interferometric

Collision energy dependence of moments of net-kaon multiplicity distributions at RHIC - STAR Collaboration (Physics Letters B, 2018)
Fluctuations of conserved quantities such as baryon number, charge, and strangeness are sensitive to the correlation length of the hot and dense matter created in relativistic heavy-ion collisions and can be used to search for the QCD critical point. We report the first measurements of the moments of net-kaon multiplicity distributions in Au+Au collisions at sNN=7.7, 11.5, 14.5, 19.6, 27, 39, 62.4, and 200 GeV. The collision centrality and energy dependence of the mean (M), variance (σ2), skewness (S), and kurtosis (κ) for net-kaon multiplicity distributions as well as the ratio σ2/M and the products Sσ and κσ2 are presented. Comparisons are made with Poisson and negative binomial baseline calculations as well as with UrQMD, a transport model (UrQMD) that does not include effects from the QCD critical point. Within current uncertainties, the net-kaon cumulant ratios appear to be monotonic as a function of collision energy.
Keywords: dept.phy; peer-reviewed

Harmonic decomposition of three-particle azimuthal correlations at energies available at the BNL Relativistic Heavy Ion Collider - STAR Collaboration (Physical Review C, 2018)
We present measurements of three-particle correlations for various harmonics in Au+Au collisions at energies ranging from sNN=7.7√sNN=7.7 to 200 GeV using the STAR detector. The quantity 〈cos(mϕ1+nϕ2−(m+n)ϕ3)〉⟨cos(mϕ1+nϕ2−(m+n)ϕ3)⟩, with ϕϕ being the azimuthal angles of the particles is evaluated as a function of sNN√sNN, collision centrality, transverse momentum, pTpT, pseudorapidity difference, ΔηΔη, and harmonics (mm and nn). These data provide detailed information on global event properties such as the three-dimensional structure of the initial overlap region, the expansion dynamics of the matter produced in the collisions, and the transport properties of the medium. A strong dependence on ΔηΔη is observed for most harmonic combinations, which is consistent with breaking of longitudinal boost invariance. An interesting energy dependence is observed when one of the harmonics m,n,m,n, or m+nm+n is equal to two, for which the correlators are dominated by the two-particle correlations relative to the second-harmonic event plane. These measurements can be used to constrain models of heavy-ion collisions over a wide range of temperature and baryon chemical potential.
Keywords: dept.phy; peer-reviewed

Beam energy dependence of rapidity-even dipolar flow in Au+Au collisions - STAR Collaboration (Physics Letters B, 2018)
New measurements of directed flow for charged hadrons, characterized by the Fourier coefficient v1, are presented for transverse momenta pT, and centrality intervals in Au+Au collisions recorded by the STAR experiment for the center-of-mass energy range sNN=7.7–200 GeV. The measurements underscore the importance of momentum conservation, and the characteristic dependencies on sNN, centrality and pT are consistent with the expectations of geometric fluctuations generated in the initial stages of the collision, acting in concert with a hydrodynamic-like expansion. The centrality and pT dependencies of v1even, as well as an observed similarity between its excitation function and that for v3, could serve as constraints for initial-state models. The v1even excitation function could also provide an important supplement to the flow measurements employed for precision extraction of the temperature dependence of the specific shear viscosity.
Keywords: dept.phy; peer-reviewed

Longitudinal double-spin asymmetries for π0 s in the forward direction for 510 GeV polarized pp collisions - STAR Collaboration (Physical Review D, 2018)
The STAR Collaboration reports measurements of the longitudinal double-spin asymmetry, ALL, for neutral pions produced at forward directions in polarized proton-proton collisions, at a center-of-mass energy of 510 GeV. Results are given for transverse momenta in the range 2<pT<10 GeV/c within two regions of pseudorapidity that span 2.65<η<3.9. These results are sensitive to the polarized gluon parton distribution function, Δg(x), down to the region of Bjorken x∼10−3. The asymmetries observed are less than ±5×10−3 in magnitude and will help constrain the contribution to the spin of the proton from polarized gluons at low x, when combined with other measurements as part of a global analysis.
Keywords: dept.phy; peer-reviewed

Longitudinal double-spin asymmetries for dijet production at intermediate pseudorapidity in polarized pp collisions at √ s = 200 GeV - STAR Collaboration (Physical Review D, 2018)
We present the first measurements of the longitudinal double-spin asymmetry ALL for dijets with at least one jet reconstructed within the pseudorapidity range 0.8<η<1.8. The dijets were measured in polarized pp collisions at a center-of-mass energy s=200 GeV. Values for ALL are determined for several distinct event topologies, defined by the jet pseudorapidities, and span a range of parton momentum fraction x down to x∼0.01. The measured asymmetries are found to be consistent with the predictions of global analyses that incorporate the results of previous RHIC measurements. They will provide new constraints on Δg(x) in this poorly constrained region when included in future global analyses. © 2018 authors. Published by the American Physical Society.
Keywords: dept.phy; peer-reviewed

Correlation measurements between flow harmonics in Au+Au collisions at RHIC - STAR Collaboration (Physics Letters B, 2018)
Flow harmonics (vn) in the Fourier expansion of the azimuthal distribution of particles are widely used to quantify the anisotropy in particle emission in high-energy heavy-ion collisions. The symmetric cumulants, SC(m,n), are used to measure the correlations between different orders of flow harmonics. These correlations are used to constrain the initial conditions and the transport properties of the medium in theoretical models. In this Letter, we present the first measurements of the four-particle symmetric cumulants in Au+Au collisions at sNN=39 and 200 GeV from data collected by the STAR experiment at RHIC. We observe that v2 and v3 are anti-correlated in all centrality intervals with similar correlation strengths from 39 GeV Au+Au to 2.76 TeV Pb+Pb (measured by the ALICE experiment). The v2–v4 correlation seems to be stronger at 39 GeV than at higher collision energies. The initial-stage anti-correlations between second and third order eccentricities are sufficient to describe the measured correlations between v2 and v3. The best description of v2–v4 correlations at sNN=200GeV is obtained with inclusion of the system's nonlinear response to initial eccentricities accompanied by the viscous effect with η/s¿0.08. Theoretical calculations using different initial conditions, equations of state and viscous coefficients need to be further explored to extract η/s of the medium created at RHIC.
Keywords: Collectivity; Correlation; Shear viscosity; dept.phy; peer-reviewed

Beam energy dependence of jet-quenching effects in Au+Au collisions at √(sNN)= 7.7, 11.5, 14.5, 19.6, 27, 39, and 62.4 GeV - STAR Collaboration (Physical Review Letters, 2018)
We report measurements of the nuclear modification factor RCP for charged hadrons as well as identified π+(−), K+(−), and p(¯p) for Au+Au collision energies of √sNN=7.7, 11.5, 14.5, 19.6, 27, 39, and 62.4 GeV. We observe a clear high-pT net suppression in central collisions at 62.4 GeV for charged hadrons which evolves smoothly to a large net enhancement at lower energies. This trend is driven by the evolution of the pion spectra but is also very similar for the kaon spectra. While the magnitude of the proton RCP at high pT does depend on the collision energy, neither the proton nor the antiproton RCP at high pT exhibit net suppression at any energy. A study of how the binary collision-scaled high-pT yield evolves with centrality reveals a nonmonotonic shape that is consistent with the idea that jet quenching is increasing faster than the combined phenomena that lead to enhancement.
Keywords: Au+Au collisions; Beam energies; Binary collisions; Charged hadrons; Colliding beam accelerators; Collision energies; Fighter aircraft; Germanium compounds; Hadrons; Lower energies; Measurements of; Nuclear modification factors; Quenching; dept.phy; peer-reviewed

Wide-field speckle techniques for small, urban telescopes - Granucci, Nicole M.; Horch, Elliott P. (Optical and Infrared Interferometry and Imaging VI, 2018)
Recent work with the NESSI speckle camera at Kitt Peak and the 'Alopeke speckle camera at Gemini-North indicates that speckle data reduction techniques can be successfully modified to produce high-resolution images over fields that are at least tens of arc seconds across. While these wide-field speckle image reconstructions are not diffraction-limited, the improvement in resolution over the seeing-limited case can be substantial. In this paper, we explore the application of these techniques to data taken with a small (0.6-m) telescope in an urban environment. Many telescopes located in urban communities, such as New Haven, Connecticut, where Southern Connecticut State University resides, have limited use scientifically due to substantial light pollution, poor seeing, poor telescope tracking, and other issues. We will present initial data using our set-up and discuss the potential for this approach for improving the imaging capabilities of small telescopes on our campus and beyond.
Keywords: Cameras; Diffraction limited; High resolution image; Image enhancement; Image reconstruction; Imaging capabilities; Interferometry; Pollution; Reduction techniques; Shift-and-add; Speckle; Speckle imaging; Telescopes; Unsharp masking; Urban environments; dept.phy; shift-and-add techniques; unsharp masking

Prospects for wireless optical intensity interferometry with the Southern Connecticut stellar interferometer - Horch, Elliott P.; Weiss, Samuel A.; Rupert, Justin D.; LaRue, Ryan; Peronio, Pietro; Rech, Ivan; Gulinatti, Angelo (Optical and Infrared Interferometry and Imaging VI, 2018)
The Southern Connecticut Stellar Interferometer (SCSI) is a two-telescope astronomical intensity interferometer that was completed in June 2016 and has been taking photon correlation data since that time. It uses single-photon avalanche diode (SPAD) detectors at the telescope focal plane and a central timing module, which records the signals from both telescopes simultaneously. In the observations taken to date, single-pixel SPADs have been connected to signal cables that stretch from each telescope to the timing module. However, we are now in the process of making the instrument “wireless” by using a separate timing module at each telescope and synchronizing the signals recorded using GPS timing cards. We have also upgraded one of the two stations with an 8-pixel SPAD device, which allows us to achieve higher count rates in a variety of observing conditions. In this paper, we report on the current state of the instrument, including engineering tests made in preparation for wireless operation, and we discuss the expected capabilities in that mode.
Keywords: Avalanche diodes; Engineering tests; Hanbury Brown and Twiss effect; Intensity interferometry; Interferometers; Interferometry; Particle beams; Photon correlation; Photons; Single photon avalanche diode; Stars; Stellar interferometers; Telescopes; Timing module; Wireless operation; Wireless-optical; dept.phy; single-photon avalanche diode (SPAD) detectors; timing correlation

Stellar photon correlation detection with the Southern Connecticut stellar interferometer - Weiss, Samuel A.; Rupert, Justin D.; Horch, Elliott P. (Optical and Infrared Interferometry and Imaging VI, 2018)
The Southern Connecticut Stellar Interferometer (SCSI) is a portable optical intensity interferometer located on the campus of Southern Connecticut State University in New Haven, Connecticut. Since its completion in 2016, the instrument has been used to take engineering data of bright stars. This paper will discuss the data collection and analysis methods, as well as the progress toward reliably measuring a significant stellar photon correlation. Vega has been the main star chosen for test observations to date because its diameter is well known by other methods, and it is not an extended source for the baselines used. The correlation peak in the processed data is compared to theoretical expectations. Given our expected sensitivity, a significant correlation peak is expected for small baselines (~2 m) to appear after a few hours of observation. So far, the observations indicate that the correlation peak is at the expected time delay, and the signal-to-noise ratio roughly scales as predicted.
Keywords: Avalanche diodes; Correlation peaks; Engineering data; Extended sources; Hanbury Brown and Twiss effect; Intensity interferometry; Interferometers; Interferometry; Optical intensities; Particle beams; Photon correlation; Photons; Quantum optics; Signal to noise ratio; Single photon avalanche diode; Stars; Stellar interferometers; dept.phy; single-photon avalanche diode (SPAD) detectors; timing correlation

Zodiacal Exoplanets in Time (ZEIT). VII. A temperate candidate Super-Earth in the Hyades Cluster - Vanderburg, Andrew; Mann, Andrew W.; Rizzuto, Aaron; Bieryla, Allyson; Kraus, Adam L.; Berlind, Perry; Calkins, Michael L.; Curtis, Jason L.; Douglas, Stephanie T.; Esquerdo, Gilbert A.; Everett, Mark E.; Horch, Elliott P.; et al. (The Astronomical Journal, 2018)
Transiting exoplanets in young open clusters present opportunities to study how exoplanets evolve over their lifetimes. Recently, significant progress detecting transiting planets in young open clusters has been made with the K2 mission, but so far all of these transiting cluster planets orbit close to their host stars, so planet evolution can only be studied in a high-irradiation regime. Here, we report the discovery of a long-period planet candidate, called HD 283869 b, orbiting a member of the Hyades cluster. Using data from the K2 mission, we detected a single transit of a super-Earth-sized (1.96 0.12 R ⊕) planet candidate orbiting the K-dwarf HD 283869 with a period longer than 72 days. As we only detected a single-transit event, we cannot validate HD 283869 b with high confidence, but our analysis of the K2 images, archival data, and follow-up observations suggests that the source of the event is indeed a transiting planet. We estimated the candidate's orbital parameters and find that if real, it has a period P ≈ 100 days and receives approximately Earth-like incident flux, giving the candidate a 71% chance of falling within the circumstellar habitable zone. If confirmed, HD 283869 b would have the longest orbital period, lowest incident flux, and brightest host star of any known transiting planet in an open cluster, making it uniquely important to future studies of how stellar irradiation affects planetary evolution. © 2018. The American Astronomical Society. All rights reserved..
Keywords: dept.phy; peer-reviewed; planetary systems; planets and satellites: detection; stars: individual (HD 283869)

Stellar companions of exoplanet host stars in K2 - Matson, Rachel A.; Howell, Steve B.; Horch, Elliott P.; Everett, Mark E. (The Astronomical Journal, 2018)
It is well established that roughly half of all nearby solar-type stars have at least one companion. Stellar companions can have significant implications for the detection and characterization of exoplanets, including triggering false positives and masking the true radii of planets. Determining the fraction of exoplanet host stars that are also binaries allows us to better determine planetary characteristics as well as establish the relationship between binarity and planet formation. Using high angular resolution speckle imaging, we detect stellar companions within ∼1 arcsec of K2 planet-candidate host stars. Comparing our detected companion rate to TRILEGAL star count simulations and known detection limits of speckle imaging, we estimate the binary fraction of K2 planet host stars to be 40%-50%, similar to that of Kepler exoplanet hosts and field stars. © 2018. The American Astronomical Society. All rights reserved.
Keywords: binaries: general; binaries: visual; dept.phy; peer-reviewed; planetary systems; techniques: high angular resolution

A spectroscopic survey of field red horizontal-branch stars - Afşar, Melike; Bozkurt, Zeynep; Topcu, Gamze Böcek; Casetti-Dinescu, Dana I.; Sneden, Christopher; Şehitog̅lu, Gizem (The Astronomical Journal, 2018)
A metallicity, chemical composition, and kinematic survey has been conducted for a sample of 340 candidate field red horizontal-branch (RHB) stars. Spectra with high resolution and high signal-to-noise ratio were gathered with the McDonald Observatory 2.7 m Tull and the Hobby-Eberly Telescope echelle spectrographs, and were used to determine effective temperatures, surface gravities, microturbulent velocities, [Fe/H] metallicities, and abundance ratios [X/Fe] for seven α and Fe-group species. The derived temperatures and gravities confirm that at least half of the candidates are true RHB stars, with (average) parameters T eff ∼ 5000 K and log g ∼ 2.5. From the α abundances alone, the thin and thick Galactic populations are apparent in our sample. Space motions for 90% of the program stars were computed from Hipparcos and Gaia parallaxes and proper motions. Correlations between chemical compositions and Galactic kinematics clearly indicate the existence of both thin-disk and thick-disk RHB stars. © 2018. The American Astronomical Society. All rights reserved..
Keywords: dept.phy; peer-reviewed; stars: abundances; stars: atmospheres; stars: evolution; stars: horizontal-branch

Speckle interferometry at SOAR in 2016 and 2017 - Tokovinin, Andrei; Mason, Brian D.; Hartkopf, William I.; Mendez, Rene A.; Horch, Elliott P. (The Astronomical Journal, 2018)
The results of speckle interferometric observations at the 4.1 m Southern Astrophysical Research Telescope in 2016 and 2017 are given, totaling 2483 measurements of 1570 resolved pairs and 609 non-resolutions. We describe briefly recent changes in the instrument and observing method and quantify the accuracy of the pixel scale and position angle calibration. Comments are given on 44 pairs resolved here for the first time. The orbital motion of the newly resolved subsystem BU 83 Aa,Ab roughly agrees with its 36-year astrometric orbit proposed by J. Dommanget. Most Tycho binaries examined here turned out to be spurious. © 2018. The American Astronomical Society. All rights reserved..
Keywords: binaries: visual; dept.phy; peer-reviewed

The NN-explore exoplanet stellar speckle imager: Instrument description and preliminary results - Scott, Nicholas J.; Howell, Steve B.; Horch, Elliott P.; Everett, Mark E. (Publications of the Astronomical Society of the Pacific, 2018)
A new speckle and wide-field imaging instrument for the WIYN telescope called NN-EXPLORE Exoplanet Stellar Speckle Imager (NESSI) is described. NESSI offers simultaneous two-color diffraction-limited imaging and wide-field traditional imaging for validation and characterization of transit and precision RV exoplanet studies. Many exoplanet targets will come from the NASA K2 and Transiting Exoplanet Survey Satellite (TESS) missions. NESSI is capable of resolving close binaries at sub-arcsecond separations down to the diffraction limit and >6 mag contrast difference in the visible band on targets as faint as 14th mag. Preliminary results from the instrument commissioning at WIYN and demonstrations of the instrument’s capabilities are presented. © 2018. The Astronomical Society of the Pacific. Printed in the U.S.A.
Keywords: Binaries (including multiple): close; Instrumentation: high angular resolution; Instrumentation: interferometers; Techniques: interferometric; Techniques: photometric; dept.phy; peer-reviewed

Transverse spin-dependent azimuthal correlations of charged pion pairs measured in p↑ + p collisions at √s=500 GeV - STAR Collaboration (Physics Letters B, 2018)
The transversity distribution, which describes transversely polarized quarks in transversely polarized nucleons, is a fundamental component of the spin structure of the nucleon, and is only loosely constrained by global fits to existing semi-inclusive deep inelastic scattering (SIDIS) data. In transversely polarized p↑+p collisions it can be accessed using transverse polarization dependent fragmentation functions which give rise to azimuthal correlations between the polarization of the struck parton and the final state scalar mesons. This letter reports on spin dependent di-hadron correlations measured by the STAR experiment. The new dataset corresponds to 25 pb−1 integrated luminosity of p↑+p collisions at s=500 GeV, an increase of more than a factor of ten compared to our previous measurement at s=200 GeV. Non-zero asymmetries sensitive to transversity are observed at a Q2 of several hundred GeV and are found to be consistent with the former measurement and a model calculation. We expect that these data will enable an extraction of transversity with comparable precision to current SIDIS datasets but at much higher momentum transfers where subleading effects are suppressed. © 2018 The Author(s)
Keywords: Di-hadron correlations; Interference fragmentation function; Transversity; dept.phy; peer-reviewed

Measurement of the ³H lifetime in Au+Au collisions at the BNL relativistic heavy ion collider - STAR Collaboration (Physical Review C, 2018)
An improved measurement of the HΛ3 lifetime is presented. In this paper, the mesonic decay modes HΛ3→He3 + π- and HΛ3→d+p+π- are used to reconstruct the HΛ3 from Au+Au collision data collected by the STAR collaboration at Relativistic Heavy Ion Collider (RHIC). A minimum χ2 estimation is used to determine the lifetime of τ=142-21+24(stat.)±29(syst.) ps. This lifetime is about 50% shorter than the lifetime τ=263±2 ps of a free Λ, indicating strong hyperon-nucleon interaction in the hypernucleus system. The branching ratios of the mesonic decay channels are also determined to satisfy B.R.(He3+π-)/(B.R.(He3+π-)+B.R.(d+p+π-))=0.32±0.05(stat.)±0.08(syst.). Our ratio result favors the assignment J(HΛ3)=12 over J(HΛ3)=32. These measurements will help to constrain models of hyperon-baryon interactions. © 2018 American Physical Society.
Keywords: dept.phy; peer-reviewed

Visible resonance Raman spectroscopy detect key molecular biomarker vibrations to characterize for human brain gliomas - Zhou, Yan; Liu, Cheng-hui; Wu, Binlin; Yu, Xinguang; Gangge Cheng; Zhang, Chunyuan; Chen, Hong; Li, Shenglin; Zong, Rui; Liang, Qijun; Zhang, Ce; Zhang, Mingqian; et al. (Biomedical Imaging and Sensing Conference, 2018)
Visible resonant Raman (VRR) spectroscopy provides an effective way to enhance Raman signal from particular bonds associated with key molecules due to changes on molecular level. This paper reports on the VRR use for detection of human brain the control and gliomas of three grades. From the RR spectra additional two molecular vibrational biomarkers at 1129cm-1 and 1338cm-1, for the four types of brain tissues are significantly different in intensity. The new RR spectral peaks can be used as molecular biomarkers to evaluate glioma grades and identify the margin of gliomas from the controls. The metabolic process of glioma cells based on the RR spectral changes may reveal the Warburg hypothesis.
Keywords: 532nm; Biomarkers; Brain; Human brain tumors; Medical imaging; Raman probe; Raman spectroscopy; Resonance Raman; Tumors; Visible resonance Raman (VRR); confical Raman probe; dept.phy; gliomas; human brain tumor

In-situ Star Formation in the Outskirts of the Large Magellanic Cloud: Gaia DR2 Confirmation. - Casetti-Dinescu, Dana I; Girard, Terrence M; Bidin, Christian Moni; Zhang, Lan; Mendez, Rene A; Vieira, Katherine; Korchagin, Vladimir I; van Altena, William F (The Astrophysical journal, 2018)
We explore the Gaia data release 2 (DR2) proper motions of six young, main-sequence stars, members of the Large Magellanic Cloud (LMC) reported by Moni Bidin et al. These stars are located in the outskirts of the disk, between 7degree and 13degree from the LMC's center where there is very low H I content. Gaia DR2 proper motions confirm that four stars formed locally, in situ, while two are consistent with being expelled via dynamical interactions from inner, more gas-rich regions of the LMC. This finding establishes that recent star formation occurred in the periphery of the LMC, where thus far only old populations were known.
Keywords: Magellanic Clouds; dept.phy; stars: early-type; stars: kinematics and dynamics

High-resolution speckle imaging - Howell, Steve B.; Horch, Elliott P. (Physics Today, 2018)
Keywords: dept.phy

A Rapid Method Based on Fluorescence Spectroscopy for Meat Spoilage Detection - Wu, Binlin; Dahlberg, Kevin; Gao, Xin; Smith, Jason; Bailin, Jacob (International Journal of High Speed Electronics and Systems, 2018)
Food spoilage is mainly caused by microorganisms, such as bacteria. In this study, we measure the autofluorescence in meat samples longitudinally over a week in an attempt to develop a method to rapidly detect meat spoilage using fluorescence spectroscopy. Meat food is a biological tissue, which contains intrinsic fluorophores, such as tryptophan, collagen, nicotinamide adenine dinucleotide (NADH) and flavin adenine dinucleotide (FAD) etc. As meat spoils, it undergoes various morphological and chemical changes. The concentrations of the native fluorophores present in a sample may change. In particular, the changes in NADH and FAD are associated with microbial metabolism, which is the most important process of the bacteria in food spoilage. Such changes may be revealed by fluorescence spectroscopy and used to indicate the status of meat spoilage. Therefore, such native fluorophores may be unique, reliable and non-subjective indicators for detection of spoiled meat. The results of the study show that the relative concentrations of all above fluorophores change as the meat samples kept in room temperature (~19°C) spoil. The changes become more rapidly after about two days. For the meat samples kept in a freezer (~ -12°C), the changes are much less or even unnoticeable over a-week-long storage.
Keywords: Amino acids; Autofluorescence; Bacteria; Biological tissues; Collagen; Flavin adenine dinucleotide; Fluorescence; Fluorescence spectroscopy; Fluorophores; Food microbiology; Meats; Metabolism; Microbial metabolism; NADH; Nicotinamide adenine dinucleotides; Nucleotides; Relative concentration; Spoilage; bacteria; collagen; dept.phy; fluorescence spectroscopy; meat food; microbial metabolism; peer-reviewed; tryptophan

Optical biopsy for prostate cancer diagnosis using fluorescence spectroscopy - Wu, Binlin; Gao, Xin; Smith, Jason (International Journal of High Speed Electronics and Systems, 2018)
Native fluorescence spectra are acquired from fresh normal and cancerous human prostate tissues. The fluorescence data are analyzed using an unsupervised machine learning algorithm such as non-negative matrix factorization. The nonnegative spectral components are retrieved and attributed to the native fluorophores such as collagen, reduced nicotinamide adenine dinucleotide (NADH), and flavin adenine dinucleotide (FAD) in tissue. The retrieved scores of the components are used to estimate the relative concentrations of the native fluorophores such as NADH and FAD and the redox ratio. A supervised machine learning algorithm such as support vector machine (SVM) is used to classify normal and cancerous tissue samples based on either the relative concentrations of NADH and FAD or the redox ratio alone. Various statistical measures such as sensitivity, specificity, and accuracy, along with the area under receiver operating characteristic (ROC) curve are used to show the classification performance. A cross validation method such as leave-one-out is used to further evaluate the predictive performance of the SVM classifier to avoid bias due to overfitting, and the accuracy was found to be 93.3%.
Keywords: Biopsy; Diseases; FAD; Factorization; Fluorescence; Fluorescence spectroscopy; Fluorophores; Learning algorithms; Learning systems; Machine learning; Matrix algebra; NADH; Nonnegative matrix factorization; Nucleotides; Optical biopsies; Optical emission spectroscopy; Prostate cancer; Prostate cancers; Redox ratio; Supervised learning; Support vector machines; Tissue; Urology; dept.phy; fluorescence spectroscopy; intrinsic tissue emission; machine learning; nonnegative matrix factorization; optical biopsy; peer-reviewed; redox ratio; support vector machine

275 candidates and 149 validated planets orbiting bright stars in K 2 campaigns 0–10 - Mayo, Andrew W.; Vanderburg, Andrew; Latham, David W.; Bieryla, Allyson; Morton, Timothy D.; Buchhave, Lars A.; Dressing, Courtney D.; Beichman, Charles; Berlind, Perry; Calkins, Michael L.; Ciardi, David R.; Crossfield, Ian J. M.; et al. (The Astronomical Journal, 2018)
Since 2014, NASA's K2 mission has observed large portions of the ecliptic plane in search of transiting planets and has detected hundreds of planet candidates. With observations planned until at least early 2018, K2 will continue to identify more planet candidates. We present here 275 planet candidates observed during Campaigns 0-10 of the K2 mission that are orbiting stars brighter than 13 mag (in Kepler band) and for which we have obtained high-resolution spectra (R = 44,000). These candidates are analyzed using the vespa package in order to calculate their false-positive probabilities (FPP). We find that 149 candidates are validated with an FPP lower than 0.1%, 39 of which were previously only candidates and 56 of which were previously undetected. The processes of data reduction, candidate identification, and statistical validation are described, and the demographics of the candidates and newly validated planets are explored. We show tentative evidence of a gap in the planet radius distribution of our candidate sample. Comparing our sample to the Kepler candidate sample investigated by Fulton et al., we conclude that more planets are required to quantitatively confirm the gap with K2 candidates or validated planets. This work, in addition to increasing the population of validated K2 planets by nearly 50% and providing new targets for follow-up observations, will also serve as a framework for validating candidates from upcoming K2 campaigns and the Transiting Exoplanet Survey Satellite, expected to launch in 2018. © 2018. The American Astronomical Society. All rights reserved.
Keywords: dept.phy; methods: data analysis; peer-reviewed; planets and satellites: detection; techniques: photometric

Chemical abundances in the leading arm of the Magellanic stream - Fox, Andrew J.; Barger, Kathleen A.; Wakker, Bart P.; Richter, Philipp; Antwi-Danso, Jacqueline; Casetti-Dinescu, Dana I.; Howk, J. Christopher; Lehner, Nicolas; D’Onghia, Elena; Crowther, Paul A.; Lockman, Felix J. (The Astrophysical Journal, 2018)
The Leading Arm (LA) of the Magellanic Stream is a vast debris field of H i clouds connecting the Milky Way and the Magellanic Clouds. It represents an example of active gas accretion onto the Galaxy. Previously, only one chemical abundance measurement had been made in the LA. Here we present chemical abundance measurements using Hubble Space Telescope/Cosmic Origins Spectrograph and Green Bank Telescope spectra of four AGN sightlines passing through the LA and three nearby sightlines that may trace outer fragments of the LA. We find low oxygen abundances, ranging from 4.0-2.0+2.0% solar to 12.6-4.16.0% solar, in the confirmed LA directions, with the lowest values found in the region known as LA III, farthest from the LMC. These abundances are substantially lower than the single previous measurement, S/H =35 ±7% solar, but are in agreement with those reported in the SMC filament of the trailing Stream, supporting a common origin in the SMC (not the LMC) for the majority of the LA and trailing Stream. This provides important constraints for models of the formation of the Magellanic System. Finally, two of the three nearby sightlines show high-velocity clouds with H i columns, kinematics, and oxygen abundances consistent with LA membership. This suggests that the LA is larger than traditionally thought, extending at least 20° further to the Galactic northwest. © 2018. The American Astronomical Society. All rights reserved.
Keywords: Galaxy: evolution; Galaxy: halo; ISM: abundances; Magellanic Clouds; dept.phy; quasars: absorption lines

Resonance raman imaging for detecting and monitoring molecular pathological changes in human brain tumors related to Warburg effect - Zhou, Yan; Liu, Cheng-hui; Zhu, Ke; Zhang, Chunyuan; Yang, Yang; Yu, Xinguang; Hu, Hailong; Cheng, Gangge; Wu, Binlin; Shi, Lingyan; Alfano, Robert R. (Optical Biopsy XVI: Toward Real-Time Spectroscopic Imaging and Diagnosis, 2018)
The goal of the research is to determine the prognostic molecular pathological changes in components and composition, for human brain glioma gradings in comparison with normal tissues in three-dimensional Raman imaging profiles by visible Resonance Raman (VRR) imaging. VRR images from twenty-five specimens including three healthy tissues, one normal control, and twenty-one glioma tissues of grades II, II-III and III-IV with histology examination were measured and investigated using WITec300R confocal micro Raman imaging system with laser excitation of 532nm. Two-dimensional RR spectral mappings performed in 20μm x 20μm generated 400 images which integrated the intensity of the specific biochemical bonds as the third dimension. The three-dimension (3D) map demonstrated the spatial distributions of three selected sets of RR spectra of molecular biomarkers, and revealed significant differences in the spectra between normal and glioma tissues of different grades due to the composition changes in key molimageecules. These RR molecular spectral fingerprints have displayed: a clear enhancement of RR vibrational modes at 1129-1131cm-1 and 2934cm-1 which are supposed to be arising from lipoproteins; evident decreased RR vibrational modes at 1442cm-1 and 2854cm-1 which are from saturated fatty acids bonds in all-grades of glioma brain tissues compared with normal tissues; and the enhanced RR spectral modes of 1129 cm-1 and 2938cm-1 which suggest contribution from lactate. These findings may provide a novel proof for anaerobic glycolysis metabolic process in brain glioma cancer tissues that has been explained by Warburg effects.
Keywords: 2-d imaging; 2D imaging; Biopsy; Brain; Gliomas; Histology; Human Brain Tissues; Human brain; Laser excitation; Molecular imaging; Resonance; Resonance Raman; Saturated fatty acids; Tumors; Visible resonance Raman (VRR); Warburg effect; Warburg effects; dept.phy

Statistical analysis and machine learning algorithms for optical biopsy - Wu, Binlin; Liu, Cheng-hui; Boydston-White, Susie; Beckman, Hugh; Sriramoju, Vidyasagar; Sordillo, Laura; Zhang, Chunyuan; Zhang, Lin; Shi, Lingyan; Smith, Jason; Bailin, Jacob; Alfano, Robert R. (Optical Biopsy XVI: Toward Real-Time Spectroscopic Imaging and Diagnosis, 2018)
Analyzing spectral or imaging data collected with various optical biopsy methods is often times difficult due to the complexity of the biological basis. Robust methods that can utilize the spectral or imaging data and detect the characteristic spectral or spatial signatures for different types of tissue is challenging but highly desired. In this study, we used various machine learning algorithms to analyze a spectral dataset acquired from human skin normal and cancerous tissue samples using resonance Raman spectroscopy with 532nm excitation. The algorithms including principal component analysis, nonnegative matrix factorization, and autoencoder artificial neural network are used to reduce dimension of the dataset and detect features. A support vector machine with a linear kernel is used to classify the normal tissue and cancerous tissue samples. The efficacies of the methods are compared.
Keywords: Artificial neural network; Biological basis; Biopsy; Cancer diagnosis; Cancerous tissues; Factorization; Learning algorithms; Learning systems; Least squares approximations; Machine learning; Matrix algebra; Neural networks; Nonnegative matrix factorization; Optical biopsies; Optical biopsy; Partial least square (PLS); Partial least squares; Principal component analysis; Resonance Raman spectroscopy; Spatial signature; Support vector machine; Support vector machines; Tissue; Tissue engineering; dept.phy

Characterization and discrimination of human breast cancer and normal breast tissues using resonance Raman spectroscopy - Wu, Binlin; Smith, Jason; Zhang, Lin; Gao, Xin; Alfano, Robert R. (Optical Biopsy XVI: Toward Real-Time Spectroscopic Imaging and Diagnosis, 2018)
Worldwide breast cancer incidence has increased by more than twenty percent in the past decade. It is also known that in that time, mortality due to the affliction has increased by fourteen percent. Using optical-based diagnostic techniques, such as Raman spectroscopy, has been explored in order to increase diagnostic accuracy in a more objective way along with significantly decreasing diagnostic wait-times. In this study, Raman spectroscopy with 532-nm excitation was used in order to incite resonance effects to enhance Stokes Raman scattering from unique biomolecular vibrational modes. Seventy-two Raman spectra (41 cancerous, 31 normal) were collected from nine breast tissue samples by performing a ten-spectra average using a 500-ms acquisition time at each acquisition location. The raw spectral data was subsequently prepared for analysis with background correction and normalization. The spectral data in the Raman Shift range of 750- 2000 cm-1 was used for analysis since the detector has highest sensitivity around in this range. The matrix decomposition technique nonnegative matrix factorization (NMF) was then performed on this processed data. The resulting leave-oneout cross-validation using two selective feature components resulted in sensitivity, specificity and accuracy of 92.6%, 100% and 96.0% respectively. The performance of NMF was also compared to that using principal component analysis (PCA), and NMF was shown be to be superior to PCA in this study. This study shows that coupling the resonance Raman spectroscopy technique with subsequent NMF decomposition method shows potential for high characterization accuracy in breast cancer detection.
Keywords: Background correction; Biopsy; Breast Cancer; Breast cancer; Breast cancer detection; Cancer diagnosis; Couplings; Decomposition methods; Diagnostic techniques; Diseases; Factorization; Learning systems; Machine learning; Matrix algebra; Molecular optical pathology; Nonnegative matrix factorization; Principal component analysis; Principal component analysis (PCA); Raman scattering; Raman spectroscopy; Resonance; Resonance Raman spectroscopy; Spectrum analysis; Support vector machine; Support vector machines; Tissue; dept.phy

Azimuthal transverse single-spin asymmetries of inclusive jets and charged pions within jets from polarized-proton collisions at √s = 500 GeV - STAR Collaboration (Physical Review D, 2018)
We report the first measurements of transverse single-spin asymmetries for inclusive jet and jet+π± production at midrapidity from transversely polarized proton-proton collisions at √s=500 GeV. The data were collected in 2011 with the STAR detector sampled from 23 pb−1 integrated luminosity with an average beam polarization of 53%. Asymmetries are reported for jets with transverse momenta 6<pT<55 GeV/c and pseudorapidity |η|<1. Presented are measurements of the inclusive-jet azimuthal transverse single-spin asymmetry, sensitive to twist-3 initial-state quark-gluon correlators; the Collins asymmetry, sensitive to quark transversity coupled to the polarized Collins fragmentation function; and the first measurement of the “Collins-like” asymmetry, sensitive to linearly polarized gluons. Within the present statistical precision, inclusive-jet and Collins-like asymmetries are small, with the latter allowing the first experimental constraints on gluon linear polarization in a polarized proton. At higher values of jet transverse momenta, we observe the first nonzero Collins asymmetries in polarized-proton collisions, with a statistical significance of greater than 5σ. The results span a range of x similar to results from semi-inclusive deep-inelastic scattering but at much higher Q2. The Collins results enable tests of universality and factorization breaking in the transverse momentum-dependent formulation of perturbative quantum chromodynamics.
Keywords: dept.phy; peer-reviewed

Proper motion of the Sextans dwarf galaxy from Subaru Suprime-Cam data - Casetti-Dinescu, Dana I.; Girard, Terrence M.; Schriefer, Michael (Monthly Notices of the Royal Astronomical Society, 2018)
We have measured the absolute proper motion of the Sextans dwarf spheroidal galaxy using Subaru Suprime-Cam images taken at three epochs, with a time baseline of ~10 yr. We astrometrically calibrate each epoch by constructing distortion-correction 'maps' from the best available Subaru Suprime-Cam dithered data sets and from Gaia Data Release 1 positions. The magnitude limit of the proper motion study is V ~ 24. The area covered is 26.7 × 23.3 arcmin2, which is still within the core radius of Sextans. The derived proper motion is (μα, μδ) = (-0.409 ± 0.050, -0.047 ± 0.058) mas yr-1. The direction of motion is perpendicular to the major axis of the galaxy. Our measurement, combined with radial velocity and distance from the literature, implies a low eccentricity orbit, with a moderate inclination to the Galactic plane, and a period of 3 Gyr. Sextans is now some 0.4 Gyr away from its pericentre (rperi ~ 75 kpc), moving towards its apocentre (rapo ~ 132 kpc). Its orbit is inconsistent with membership to the vast polar structure of Galactic satellites. © 2018 The Author(s).
Keywords: Astrometry; Galaxies: dwarf; Galaxies: individual: Sextans; Proper motions; dept.phy; peer-reviewed

High performance materials and devices for high-speed electronic systems - Jain, F; Broadbridge, C; Tang, H; Gherasimova, M (Selected Topics in Electronics and Systems, 2018)
In this review volume, the editors have included the state-of-the-art research and development in nano composites, and optical electronics written by experts in the field. In addition, it also covers applications for emerging technologies in High-Speed Electronics. In summary, topics covered in this volume includes various aspects of high performance materials and devices for implementing High-Speed Electronic systems. © 2019 by World Scientific Publishing Co. Pte. Ltd. All rights reserved.
Keywords: Emerging technologies; High performance material; High-speed electronics; Materials; Nanocomposites; Optical electronics; State of the art; dept.phy

Exploring multiphoton microscopy as a novel tool to differentiate chromophobe renal cell carcinoma from oncocytoma in fixed tissue sections - Jain, Manu; Robinson, Brian D.; Wu, Binlin; Khani, Francesca; Mukherjee, Sushmita (Archives of Pathology & Laboratory Medicine, 2018)
Context.-Distinguishing chromophobe renal cell carcinoma (chRCC), especially in the presence of eosinophilic cytoplasm, from oncocytoma on hematoxylin-eosin can be difficult and often requires time-consuming ancillary procedures that ultimately may not be informative. Objective.-To explore the potential of multiphoton microscopy (MPM) as an alternative and rapid diagnostic tool in differentiating oncocytoma from chRCC at subcellular resolution without tissue processing. Design.-Unstained, deparaffinized tissue sections from 27 tumors (oncocytoma [n = 12], chRCC [n = 12], eosinophilic variant of chRCC [n = 1], and atypical oncocytic renal neoplasm [n = 2]) were imaged with MPM. Morphologic evaluation and automated quantitative morphometric analysis were conducted to distinguish between chRCC and oncocytoma. Results.-The typical cases of oncocytomas (12 of 12) and chRCC (12 of 12) could be readily differentiated on MPM based on the morphologic features similar to hematoxylin-eosin. The most striking MPM signature of both of the tumors was the presence of autofluorescent intracytoplasmic granules, which are not seen on hematoxylin-eosin-stained slides. Although we saw these granules in both types of tumors, they appeared distinct, based on their size, shape, cytoplasmic distribution, and autofluorescence wavelengths, and were valuable in arriving at a definitive diagnosis. For oncocytomas and chRCC, high diagnostic accuracies of 100% and 83.3% were achieved on blinded MPM and morphometric analysis, respectively. Conclusions.-To the best of our knowledge, this is the first demonstration of MPM to distinguish chRCC from oncocytoma in fixed tissues. Our study was limited by small sample size and only a few variants of oncocytic tumors. Prospective studies are warranted to assess the utility of MPM as a diagnostic aid in oncocytic renal tumors. © Copyright 2018 College of American Pathologists.
Keywords: Adenoma, Oxyphilic; Carcinoma, Renal Cell; Diagnosis, Differential; Humans; Kidney Neoplasms; Microscopy, Fluorescence, Multiphoton; Tissue Fixation; dept.phy; differential diagnosis; human; kidney tumor; multiphoton microscopy; oncocytoma; pathology; peer-reviewed; procedures; renal cell carcinoma; tissue fixation

Assessment of basal cell carcinoma from normal human skin tissues using Resonance Raman spectroscopy - Liu, Chenghui; Wu, Binlin; Sordillo, Laura A; Boydstonwhite, Susie; Sriramoju, Vidyasagar; Zhang, Chunyuan; Beckman, Hugh; Zhang, Lin; Pei, Zhe; Shi, Lingyan; Alfano, R R (OSA - The Optical Society, 2018)
VRR spectroscopy was used for BCC and normal skin tissues with 532nm excitation. The spectra showed significant changes in collagen, carotenoids and lipids. These enhanced fingerprints demonstrate a potential use as label-free pathology method. © 2018 The Author(s).
Keywords: Basal cell carcinoma; Histology; Human skin; Label free; Normal skin; Resonance Raman spectroscopy; Tissue; dept.phy

A pilot study for distinguishing chromophobe renal cell carcinoma and oncocytoma using second harmonic generation imaging and convolutional neural network analysis of collagen fibrillar structure - Wu, Binlin; Judd, Nicolas; Smith, Jason; Icaza, Michael; Mukherjee, Sushmita; Jain, Manu; Gallagher, Ryan M; Szeligowski, Richard V (2018)
A clear distinction between oncocytoma and chromophobe renal cell carcinoma (chRCC) is critically important for clinical management of patients. But it may often be difficult to distinguish the two entities based on hematoxylin and eosin (H and E) stained sections alone. In this study, second harmonic generation (SHG) signals which are very specific to collagen were used to image collagen fibril structure. We conduct a pilot study to develop a new diagnostic method based on the analysis of collagen associated with kidney tumors using convolutional neural networks (CNNs). CNNs comprise a type of machine learning process well-suited for drawing information out of images. This study examines a CNN model's ability to differentiate between oncocytoma (benign), and chRCC (malignant) kidney tumor images acquired with second harmonic generation (SHG), which is very specific for collagen matrix. To the best of our knowledge, this is the first study that attempts to distinguish the two entities based on their collagen structure. The model developed from this study demonstrated an overall classification accuracy of 68.7% with a specificity of 66.3% and sensitivity of 74.6%. While these results reflect an ability to classify the kidney tumors better than chance, further studies will be carried out to (a) better realize the tumor classification potential of this method with a larger sample size and (b) combining SHG with two-photon excited intrinsic fluorescence signal to achieve better classification. © COPYRIGHT SPIE. Downloading of the abstract is permitted for personal use only.
Keywords: Biomedical signal processing; Biopsy; Chromophobe renal cell carcinoma; Classification accuracy; Collagen; Convolution; Convolutional Neural Networks (CNN); Convolutional neural network; Convolutional neural networks (CNN); Fluorescence; Harmonic analysis; Harmonic generation; Intrinsic fluorescence signals; Kidney tumor; Learning systems; Machine learning; Multiphoton microscopy; Multiphoton microscopy (MPM); Multiphoton processes; Neural networks; Nonlinear optics; Patient monitoring; Renal cell carcinoma; Renal oncocytoma; Second harmonic generation; Tumor classification; Tumors; dept.phy

Diagnosis of glioma brain cancer using visible resonance Raman spectroscopy - Zhou, Yan; Wu, Binlin; Liu, Chenghui; Yu, Xinguang; Cheng, Gangge; Wang, Kai; Zhang, Chunyuan; Shi, Lingyan; Alfano, R R (OSA, 2018)
Resonance Raman spectroscopy using 532nm excitation was used to distinguish normal brain tissue from different grades of glioma tissues. Principal component analysis was used to analyze the spectral data and achieved high accuracy. © 2018 The Author(s).
Keywords: Brain cancer; Brain tissue; Different grades; Glioma tissues; High-accuracy; Principal component analysis; Raman spectroscopy; Resonance Raman spectroscopy; Spectral data; Tumors; dept.phy